A Novel Mix of Polyphenols and Micronutrients Reduces Adipogenesis and Promotes White Adipose Tissue Browning via UCP1 Expression and AMPK Activation - Francesca Pacifici; Gina Malatesta; Caterina Mammi; Donatella Pastore; Vincenzo Marzolla; Camillo Ricordi; Francesca Chiereghin; Marco Infante; Giulia Donadel; Francesco Curcio; Annalisa Noce; Valentina Rovella; et al. (Cells, 2023)
Background: Obesity is a pandemic disease characterized by excessive severe body comorbidities. Reduction in fat accumulation represents a mechanism of prevention, and the replacement of white adipose tissue (WAT) with brown adipose tissue (BAT) has been proposed as one promising strategy against obesity. In the present study, we sought to investigate the ability of a natural mixture of polyphenols and micronutrients (A5+) to counteract white adipogenesis by promoting WAT browning. Methods: For this study, we employed a murine 3T3-L1 fibroblast cell line treated with A5+, or DMSO as control, during the differentiation in mature adipocytes for 10 days. Cell cycle analysis was performed using propidium iodide staining and cytofluorimetric analysis. Intracellular lipid contents were detected by Oil Red O staining. Inflammation Array, along with qRT-PCR and Western Blot analyses, served to measure the expression of the analyzed markers, such as pro-inflammatory cytokines. Results: A5+ administration significantly reduced lipids’ accumulation in adipocytes when compared to control cells (p < 0.005). Similarly, A5+ inhibited cellular proliferation during the mitotic clonal expansion (MCE), the most relevant stage in adipocytes differentiation (p < 0.0001). We also found that A5+ significantly reduced the release of pro-inflammatory cytokines, such as IL-6 and Leptin (p < 0.005), and promoted fat browning and fatty acid oxidation through increasing expression levels of genes related to BAT, such as UCP1 (p < 0.05). This thermogenic process is mediated via AMPK-ATGL pathway activation. Conclusion: Overall, these results demonstrated that the synergistic effect of compounds contained in A5+ may be able to counteract adipogenesis and then obesity by inducing fat browning.